F7. EEG-INDEXED AUDITORY NOVELTY DETECTION DEFICITS IN EARLY-PHASE PSYCHOSIS. (9th April 2019) - Riel, Hayley; Tibbo, Philip; Fisher, Derek
Abstract: Background: Research has suggested that deficits in auditory novelty detection, measured as mismatch negativity (MMN) and novelty P300, are present in individuals diagnosed with chronic schizophrenia as well as early-phase psychosis (EPP). However, reports of auditory change detection deficits in EPP are inconsistent and need replication. The goal of this study was to further investigate whether MMN and novelty P300 measures deficits exist in an EPP population relative to healthy controls. Methods: A total of 17 participants aged 18 to 35 with EPP were recruited from the Nova Scotia Early Psychosis Program. Twenty-three healthy controls of equivalent age were recruited from the community. Electrophysiological recordings of auditory change detection were measured during the passive presentation of a novelty oddball paradigm. Within the novelty paradigm, standard (P = 0.8) and deviant tones (P = 0.1), in addition to novel environmental sounds (i.e., a dog barking; P = 0.1) were presented. Our endpoints of interest were amplitudes and latencies of the MMN (deviant and novel) and novelty P300 (novel only). Results: The EPP group exhibited reduced novelty MMN amplitudes (p = .05), as well as reduced novelty P300 amplitude (p < .01), relative to healthy controls. Additionally, preliminary analysis of the healthy controls revealed significant sex differences for novelty MMN at frontal and central electrode sites (p < .015; females > males) and novelty P300 at frontal sites (p < .05; females < males). There was an insufficient male:female split in our EPP sample to conduct similar analyses. Discussion: Overall, our findings support previous reports of reduced MMN in EPP, albeit only to novel environmental sounds. We also corroborate previous findings of reduced novelty P300 in this population. Preliminary analysis of our healthy controls revealed sex differences for both MMN and novelty P300. Future work should whether these sex differences in electrocortical function extend to disorders of psychosis.